The Assessment of Sleep Quality among Anesthesia Nurses in the Central Surgical Installation Room at Banyumas Region Hospital - Panji Wicaksono Aji; Dwi Novitasari; Roro Lintang Suryani (Inspirasi Foundation, 2023)
Introduction: Invertebrate creatures and humans still conserved sleep. Sleep time in humans becomes shorter, faster, and the quality decreases with age. Good quality sleep can improve mental health. Fatigue can result in poor sleep quality of nurse anesthesiologist which can certainly endanger the patient and nurse anesthesiologist himself. Objective: This study aims to identify the description of sleep quality based on gender, age, and period of work in the Central Surgical Installation Room at Banyumas Regional Hospital. Method: This research method is descriptive quantitative, data was collected online using googleform giving questionnaires with a cross sectional approach design. Result: The results showed that the sleep quality of nurse anesthesiologists based on sex was most in the male sex as many as 16 (41%) results were poor. The highest age category was in late adulthood as many as 11 (28%) respondents with poor sleep quality. The category of working time is the most in 5 years of work as many as 16 (41%) respondents with poor sleep quality. As a result of the sleep disorders component, anesthesiologists experienced many bad sleep disorders as many as 30 (76.9%) respondents. Conclusion: The quality of sleep in the anesthesiologist of the Central Surgical Installation Room at Banyumas Regional Hospital was classified as poor sleep quality